Representasi Diskriminasi Perbedaan Ras dalam Film Green Book: (Analisis Semiotika Charles Sanders Pierce) - Ratri Pramudita; Arief Hidayatullah; Junaidin Junaidin (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines racial discrimination representation in the 2018 film "Green Book" using Charles Sanders Pierce's semiotic analysis. The film portrays racism in 1960s America through the relationship between Tony Lip, a white Italian-American, and Dr. Don Shirley, a black classical pianist. The research identifies examples of both individual racism (racial prejudice, stereotyping, discrimination, and harassment) and institutional racism through selected scenes. Using Pierce's Triangle Meaning framework of Sign, Object, and Interpretant, the analysis reveals how racism manifested through both personal interactions and governmental policies like Jim Crow laws. Individual racism appears through characters' prejudices about black people's trustworthiness, stereotyping Germans, segregated facilities enforcement, and physical violence against black individuals. Institutional racism is demonstrated through "whites only" policies restricting black citizens' movements after dark. The film shows how discrimination affected African Americans so severely they required travel guides (the "Green Book") to navigate safely through the segregated South. This research concludes that racism depicted in the film stemmed from both governmental regulations and societal prejudices, resulting in discriminatory treatment that significantly impacted the black community's daily life and dignity.